1999
DOI: 10.1054/npep.1999.0053
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 (7–36) amide: a central regulator of satiety and interoceptive stress

Abstract: INTRODUCTIONIngestion of food is a necessary and pleasant occupation that allows humans and other species to maintain caloric homeostasis and a certain level of body weight. Ironically, in doing so, one's 'milieu interieur' is put at risk because meal-induced fuel excursions can have deleterious effects on metabolic (e.g. glycosylation causing loss of enzymatic efficacy) and cardiovascular (e.g. triglyceride accumulation, increased blood pressure, etc.) processes. 1,2 To reduce these perturbations to a minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(16 citation statements)
references
References 64 publications
0
15
1
Order By: Relevance
“…Consistent with this, behavioral and physiological responses to centrally administered GLP1 include pituitary stress hormone release, autonomic responses, hypophagia, and anxiety-like behavior (Maniscalco et al 2012; Kinzig et al 2003; Donahey et al 1998; Gulpinar et al 2000; Larsen et al 1997b; Mietlicki-Baase et al 2013; Moller et al 2002; Nakade et al 2006, 2007; Rinaman 1999a; Schick et al 2003; Seeley et al 2000; Thiele et al 1998; Turton et al 1996). A suggested role for central GLP1-R signaling pathways in body energy balance (Tang-Christensen et al 2001; Hayes 2012; Meeran et al 1999; vanDijk and Thiele 1999) also is supported by evidence in rats and mice implicating central GLP1 in temperature regulation (Rinaman and Comer 2000; O’Shea et al 1996) and glucose homeostasis (Sandoval et al 2008). GLP1-R agonists enhance both excitatory and inhibitory synaptic inputs to identified neurons through presynaptic stimulation of transmitter release from axon terminals (Wan et al 2007; Acuna-Goycolea and van den Pol 2004), and postsynaptic effects of GLP1 on neuronal activity also are reported (Acuna-Goycolea and van den Pol 2004; Riediger et al 2010; Hayes 2012).…”
Section: Discussionmentioning
confidence: 90%
“…Consistent with this, behavioral and physiological responses to centrally administered GLP1 include pituitary stress hormone release, autonomic responses, hypophagia, and anxiety-like behavior (Maniscalco et al 2012; Kinzig et al 2003; Donahey et al 1998; Gulpinar et al 2000; Larsen et al 1997b; Mietlicki-Baase et al 2013; Moller et al 2002; Nakade et al 2006, 2007; Rinaman 1999a; Schick et al 2003; Seeley et al 2000; Thiele et al 1998; Turton et al 1996). A suggested role for central GLP1-R signaling pathways in body energy balance (Tang-Christensen et al 2001; Hayes 2012; Meeran et al 1999; vanDijk and Thiele 1999) also is supported by evidence in rats and mice implicating central GLP1 in temperature regulation (Rinaman and Comer 2000; O’Shea et al 1996) and glucose homeostasis (Sandoval et al 2008). GLP1-R agonists enhance both excitatory and inhibitory synaptic inputs to identified neurons through presynaptic stimulation of transmitter release from axon terminals (Wan et al 2007; Acuna-Goycolea and van den Pol 2004), and postsynaptic effects of GLP1 on neuronal activity also are reported (Acuna-Goycolea and van den Pol 2004; Riediger et al 2010; Hayes 2012).…”
Section: Discussionmentioning
confidence: 90%
“…95, 96 As noted previously, GLP-1 may have direct effects in the CNS because it can reach the brainstem via the subfornical organ and AP, which lack a typical blood–brain barrier. 97 A direct central effect of GLP-1 is supported by results from a study which showed that only the effect of intraperitoneal, but not intravenous (intraportal), GLP-1 on eating required vagal afferent signaling.…”
Section: Mechanisms Of Glp-1 Inhibition Of Satiety/food Intakementioning
confidence: 90%
“…For example, GLP-1 has an inhibitory effect on gastric emptying and therefore slows glucose absorption [26]. Moreover, GLP-1 reportedly has an effect on satiety and on reducing food intake [2730]. Further study will be needed to understand the effect of weight loss on fasting incretin hormone concentrations.…”
Section: Discussionmentioning
confidence: 99%